2018
DOI: 10.1007/s12298-018-0590-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for physiological and biochemical traits related to grain yield under control and terminal heat stress conditions in bread wheat (Triticum aestivum L.)

Abstract: In order to detect genomic regions with different effects for some of the physiological and biochemical traits of wheat, four experiments were conducted at Research Farm of Agricultural and Natural Resources Research Center of Zabol in 2015-2016 and 2016-2017 growing seasons. The experiments were carried out using four alpha lattice designs with two replications under non-stress and terminal heat stress conditions. Plant materials used in this study included 167 recombinant inbred lines and their parents ('Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
5
21
0
1
Order By: Relevance
“…Among the diverse heavy metals-stress and waterstress tolerance traits targeted in crop breeding, CMS is regarded as a physiological parameter which is mostly affected (Singh et al 2016). QTLs for CMS have been previously reported on LGs 1D, 4B, 5A, 6B, and 7A for drought tolerance across different wheat populations under field conditions (Elshafei et al 2013;Talukder et al 2014;Sohrabi et al 2018), which were in accordance with our results. Variations in WSC content are largely genetically determined.…”
Section: Qtl Mapping Of Flag Leaf Morpho-physiological Traits Associasupporting
confidence: 92%
See 1 more Smart Citation
“…Among the diverse heavy metals-stress and waterstress tolerance traits targeted in crop breeding, CMS is regarded as a physiological parameter which is mostly affected (Singh et al 2016). QTLs for CMS have been previously reported on LGs 1D, 4B, 5A, 6B, and 7A for drought tolerance across different wheat populations under field conditions (Elshafei et al 2013;Talukder et al 2014;Sohrabi et al 2018), which were in accordance with our results. Variations in WSC content are largely genetically determined.…”
Section: Qtl Mapping Of Flag Leaf Morpho-physiological Traits Associasupporting
confidence: 92%
“…Intensities of expression of quantitative traits are affected by the epistatic and QTL 9 environment interactions effects which are important genetic components (Li et al 2014). Epistasis and AE studies have been conducted in wheat for CT and GYLD (Tahmasebi et al 2016), FLMrelated traits (Yang et al 2016), CMS, and WSC (Sohrabi et al 2018). In most of the previous studies carried out on QTL mapping in bread wheat, the associated interactions (AA, AE, and AAE) were not totally investigated (e.g.…”
Section: Qtls With Additive 3 Environment Interaction and Epistatic Ementioning
confidence: 99%
“…The common QTLs in uenced GY, WSC, CMS, PRO, and Fv/Fm in both environments and were found on chromosomes 2B, 2D, 4A, 4B, 5B, and 6A. However, numerous QTLs with signi cant impacts (such as QChl-4A) were found for different traits in just one of the two environmental conditions 27 (Hassan et al, 2018). Under heat and drought stress, Pinto et al 2010 found multiple environmentsensitive QTLs for grain yield and yield-related characteristics in this group 13 .…”
Section: Qtl Comparison Between Conditionsmentioning
confidence: 94%
“…Similarly, the SPAD QTLs were dispersed on 2D and 7D, explained 4.3%-17.3% (PVE) of the total variation in chlorophyll content 29 (Tahmasebi et al, 2016). Heat tolerance in eld crops, such as bread wheat, is linked to a number of physiological, biochemical, and morphological characteristics 27 (Hassan et al, 2018). As a result, we examined a variety of physiological and developmental variables to learn more about the components that in uence heat responsiveness to grain weight and the basis of the QTL-controlled tolerance mechanisms.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Об эффективности метода говорит частота его использования. AFLP активно и успешно применяется для оценки межсортовой вариабельности у многих сельскохозяйственных культур, в том числе пшеницы (6), ячменя (7), гороха (8,9), перца (10,11).…”
unclassified